Biochar From Sugarcane Bagasse and Arbuscular Mycorrhizal Fungi on Growth and Nutrient Status of Cacao (Theobroma cacao L.) Seedlings Under Nursery Conditions. - Aggangan, N.S
Most soils in the Philippines are acidic and are low in nutrients to support vigorous plant growth. The effect of applying both biochar and mycorrhizal fungi on plants under acidic soil is not yet well established. This study aimed to determine the influence of biochar from sugarcane bagasse (BSB) and arbuscular mycorrhizal fungi (AMF) on the growth traits, mycorrhization, and nitrogen (N) and phosphorus (P) uptakes of cacao seedlings under nursery conditions. The mycorrhizal soil inoculant contained 12 species belonging to the genera Glomus, Gigaspora, Acaulospora, and Entrophospora. These AMF were developed and commercially produced at the National Institute of Molecular Biology and Biotechnology (BIOTECH), University of the Philippines Los Baños (UPLB), Laguna, Philippines. The experiment was conducted for 6 mo in a nursery following a two-factor randomized complete block design with 12 replicates. Seeds of cacao var. UF18 were sown in polybags filled with 200 g oven-sterilized soil-sand mixture. After 1 mo, seedlings were transferred in polybags filled with 2 kg oven-sterilized acidic soil amended with nil to 15% biochar. The soil-biochar mixture was cured for 2 wk prior to seedling transfer. Inoculation with AMF was done during this stage, placed directly beneath the roots. At 6 mo, AMF inoculated cacao seedlings grown in BSB amended soil gave lighter biomass than those grown in no biochar soil. This may suggest that BSB could possibly induce mycorrhizal parasitism as there was a high mycorrhizal infection rate while constitutively having low N and P uptakes. However, the exact mechanisms on how biochar could possibly promote parasitism on plants inoculated with AMF are not yet known. Thus, further studies must be conducted.